Strategi Komunikasi OZ Radio Jakarta dalam Mempertahankan Eksistensi Siaran di Era Media Digital - Rafinsyah Mauludi Munandar (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The development of digital technology has shifted media consumption patterns, including radio media, which now faces a big challenge to remain relevant in the era of media convergence. OZ Radio Jakarta is one of the private radio stations that continues to survive with adaptive communication strategies. This research aims to find out the communication strategy of OZ Radio Jakarta in maintaining its broadcast existence in the digital media era. The research used a qualitative approach with a case study method. Data collection techniques were conducted through in-depth interviews with three key informants, namely the producer, social media team, and marketing team of OZ Radio Jakarta, as well as documentation and observation. Data analysis used Communication Strategy theory (Effendy, 2000), Niche Theory (Dimmick, 2003). The results showed that OZ Radio Jakarta carries out a coordinated internal and external communication strategy, utilizes social media as an audience participatory space, and maintains the emotional value of conventional broadcasts. The strategy has succeeded in maintaining OZ Radio Jakarta's existence as an adaptive, creative, and capable audio media in a competitive digital media landscape. Keywords: Communication Strategy, Digital Media, Existence, Radio.